“Like sand through an hourglass, so are the days of our lives”: Youth, religion, and social capital in South Africa - J. Beukes (Acta Theologica)
South Africa has experienced significant transformations, including the dismantling of the apartheid system and the transition to a democratic regime. Despite progress, South Africa still struggles with inequality and fostering social cohesion. Social capital refers to networks, relationships, and customs that enable collaboration. Young people’s networks and connections shape their social and economic success. Social capital helps young people establish friendships and access to resources. Religion improves social capital in many places. This article analyses the concept of social capital imposed by religious institutions and their practices in various communities, larger societies, and younger generations. It aims to investigate the distinctive role of religion in enhancing social capital in an effort to demarginalise youth. The article examines the correlation between youth, religion, and social capital in South Africa, focusing on how religious practices and beliefs can affect young people’s sense of social connectedness and community.